Relações entre preconceito religioso, preconceito racial e autoritarismo de direita: uma análise psicossocial - Cavalcanti, Ana Paula Rodrigues (2016)
The number of religious intolerance denouncements has recently increased, especially those against African-Brazilian religions. Would be this kind of prejudice related to Brazilian racial prejudice? Justified discrimination theory alleges that the legitimating myth to disguise racial prejudice, on this case, would be the demonization of AfricanBrazilian religious beliefs. Under this theory it was investigated the degree of relationship between African-Brazilian religions discrimination, racial prejudice, prosperity theology, kind and strength of religion, and right-wing authoritarianism as well as which of these factors mediates the relation of religion/religiosity and discrimination. To accomplish this, two studies were done (college students, N = 300; devotees of different kinds of Christianism, N = 519) using a specific scale to measure each construct. The AfricanBrazilian religions discrimination scale was well-succeed (α = 0,84) as well as the religion/religiosity one (α = 0,94). Neopentecostals and Protestants discriminate more African-Brazilian religions. Catholics, atheists and non-religious are more tolerant. It was concluded that neither racism, nor prosperity theology, but right-wing authoritarianism construct is the mediator between religion/religiosity and religious discrimination (Z of Sobel = 7,95; p = 0,001 e 8,24; p = 0,01 in each study, respectively). It is the first study of this kind in Brazil, and a surprising result that demands prudency on its interpretation.